Feasibility of the virtual reality-based assessments in patients with panic disorder - Kim, Byung-Hoon; Kim, Jae-Jin; Oh, Jooyoung; Kim, Seung-Hyun; Han, Changsu; Jeong, Hyun-Ghang; Lee, Moon-Soo; Kim, Junhyung (Frontiers in Psychiatry, 2023)
Recurrences and diagnostic instability of panic disorder (PD) are common and have a negative effect on its long-term course. Developing a novel assessment tool for anxiety that can be used in a multimodal approach may improve these problems in panic disorder patients. This study assessed the feasibility of virtual reality-based assessment in panic disorder (VRA-PD). Twenty-five patients with PD (ANX group) and 28 healthy adults (CON group) participated in the study. VRA-PD consisted of four modules based on the key components of cognitive behavior therapy for an anxiety disorder: “Baseline evaluation module” (M0), “Daily environment exposure module” (M1), “Relaxation module” (M2), and “Interoceptive exposure module” (M3). Multiple evaluations, including self-rating anxiety scores (AS) and physiological responses (heart rate variability (HRV) index), were performed in three steps at M1, M2, and M3, and once at M0. Comparisons between patients with PD and healthy controls, factor analysis of variables in VRA-PD, changes in responses within modules, and correlation analysis between variables in VRA-PD and anxiety symptoms assessed by psychological scales were performed. All participants completed the VRA-PD without discontinuation. The ANX group reported significantly higher AS for all steps and a smaller HRV index in M1 (steps 1 and 2) and M2 (step 1). Repeated-measures analysis of covariance (ANCOVA) revealed significant interaction effects for AS in M1 (F = 4.09, p = 0.02) and M2 (F = 4.20, p = 0.02), and HRV index in M2 (F = 16.22, p < 0.001) and M3 (F = 21.22, p = 0.02). The HRV index only indicated a good model fit for the three-factor model, reflecting the construct of the VRA-PD. Both AS and HRV indexes were significantly correlated with anxiety and depression symptoms. The current study provides preliminary evidence that the VRA-PD could be a valid anxiety behavior assessment tool.